Sustainable Food Consumption of German Millennials: Exploring the "Attitude Behavior Gap" - Max Lindner (Junior Management Science (JUMS), 2021)
This thesis picked up on the recent trend of sustainability and sustainable development by investigating the sustainable food consumption of German Millennials regarding an assumed gap between their attitude and their actual consumer behavior. Based on the Theory of Planned Behavior, a multi-step, qualitative research process was developed in order to find explanations for the attitude behavior gap. The process triangulated data from questioning ten German Millennial consumers via qualitative interviews, observing these consumers during a regular grocery shopping trip and analyzing the products they bought. The study revealed the following barriers preventing the participants from consuming according to their attitude: price, lack of knowledge on part of the consumers, insufficient sustainable product ranges, consumers minimizing the time spent for grocery shopping, habitualized purchase decisions and in exceptional cases a desire for unsustainable products. Accordingly, recommendations were derived for sustainable food manufacturers and supermarket chains, public policy and consumers. Additionally, this thesis contributes to consumer research on the attitude behavior gap as well as on behavioral research by applying and extending the Theory of Planned Behavior.
Keywords: 650; Sustainable consumption; attitude behavior gap; consumer behavior; food consumption Verbal Protocol Analysis; Theory of Planned Behavior